COVID-19 pansinusitis with abducens paralysis - Seferoglu, Meral; Koca, Nizameddin; Coşkun, Yasemin; Hakyemez, Bahattin (The European Research Journal, 2022)
Increasing numbers of the papers indicate that SARS-CoV-2 also causes neurological symptoms; the underlying mechanism has not been elucidated yet. Hypothetic mechanisms to explain the CNS involvement of SARS-CoV-2 include the neurotropic mechanisms and the cytokine storm developing during the disease process. A middle age female patient applied to the emergency department with complaints of eye pain, a double, foggy, and blurred vision and a severe throbbing headache. The outward gaze was found to be limited in her right eye. Nasopharyngeal swab for SARS-CoV-2 RNA was positive, radiological findings were supported the COVID pneumonia and diffuse sinonasal inflammation. Cranial imaging showed thickening and contrast involvement in the cavernous sinus in the postcontrast series. While shortness of breath improved, and the headache was completely resolved on the 10th day of treatment the right eye outward gaze restriction was continued. The control MRI reveals a significant reduction in cavernous thickening and contrast enhancement and complete resolution in dural thickening. In our case of COVID, cranial nerve involvement and pansinusitis developed without cytokine storm findings suggests that the virus has spread to the cavernous sinuses and dura by regional neighborhood. Neurological symptoms may appear as the first symptom of COVID.